European trainee exchange: experiences due the ENTOG exchange programme 2015 in Utrecht, the Netherlands - Veldink, Hendrik; Jan, Ziga; Lermann, Johannes; Nijkamp, J. W.; Schott, Sarah (Archives of gynecology and obstetrics, 2016)
The European Network of Trainees in Obstetrics and Gynaecology (ENTOG) is a Europe wide association of trainees in gynaecology and obstetric. It is closely associated with the European Board and College of Obstetrics and Gynaecology. Both organisations aim to improve the training in gynaecology and obstetrics as the fundamental step to overcome large differences in women’s health across Europe. Annually, ENTOG meeting takes place which brings together trainees from the member countries to share their professional experience. The training session of the meeting which is preceded by an exchange programme. The exchange programme aims to learn something about the everyday work of the host country.
Published online: 2 November 2015
Gesehen am 04.06.2020